Temperature and strain gradients through Lesser Himalayan rocks and across the Main Central thrust, south central Bhutan: Implications for transport‐parallel stretching and inverted metamorphism. Issue 8 (16th August 2016) - Long, Sean P.; Gordon, Stacia M.; Young, John P.; Soignard, Emmanuel
Abstract: In order to understand mass and heat transfer processes that operated during Himalayan orogenesis, we collected temperature, finite and incremental strain, and kinematic vorticity data through a 5 km thickness of Lesser and Greater Himalayan rocks in southern Bhutan. This transect crosses two major shear zones, the Main Central thrust (MCT) and Shumar thrust (ST). Raman spectroscopy on carbonaceous material and garnet‐biotite thermometry are integrated with deformation temperatures from quartz petrofabrics. These data define inverted field gradients that correspond in structural position with the MCT and ST, which are separated by sections in which temperatures remain essentially constant. Temperatures increase from 400–500°C to 700–750°C between 675 m below and 200 m above the MCT. This defines a 269 ± 44°C/km inverted gradient, interpreted to have formed via high‐magnitude ( 100–250 km) shearing on a discrete MCT zone delineated by the limits of inverted metamorphism. Temperatures increase from 300–400°C to 400–530°C across the ST, which is attributed to differences in maximum burial depth of hanging wall and footwall rocks. Strain and vorticity data indicate that Lesser and Greater Himalayan rocks were deformed by layer‐normal flattening. Transport‐parallel lengthening and foliation‐normal shortening increase from 38–71% to 36–49%, respectively, between 2.3 and 1.0 km below the MCT. The MCT acted as a "stretching fault, " with translation on the order of hundreds of kilometers accompanied by transport‐parallel stretching of footwall and hanging wall rocks on the order of tens of kilometers. This demonstrates that stretching accommodated between major shear zones can make a significant contribution to cumulative mass transfer. Key Points: The MCT and ST exhibit inverted thermal field gradients, which are separated by sections of constant temperature The steep MCT gradient formed from 100 to 250 km of translation on a 1 km thick shear zone, delineated by the limits of inverted metamorphism Translation on the MCT was accompanied by tens of km of transport‐parallel stretching of hanging wall and footwall rocks